Measuring Retail Service Quality of OIWAK Store by Importance and Performance Analysis - Zulkarnaen, Faisal Rasyid; Aldianto, Leo (Journal of Business and Management, 2012)
The growth of modern markets is higher today that result in increased competition among retail businesses. Oiwak as a retail store in Indonesia that sells fresh fish as its main product must be able to compete and win in this state. Moreover Oiwak store should be able to compete with firms of different types of retail that sells a wide range of products. As a retail company that sells fresh fish where this type of product is not common in Indonesian, the store should be able to read customer characteristics and analyze customer satisfaction levels based on the quality of services provided which eventually could have implications on marketing strategies to satisfy the needs of its customers. This research is to assess the response of a sample of visitors with 80 respondents through the analysis of customer satisfaction of the attributes of service quality using importance-performance analysis which compared between expectations and the actual reality of customer perception. Research result would recommend management of Oiwak store to improve attributes the performance of service is still below of customer’s expectation first which are in dimension of Reliability and Personal Interaction specifically in error purchase recording and the knowledge of the employee. Key words: Retail, Service Quality, Importance-Performance Analysis Category: Performance Management, Marketing